2020
DOI: 10.1080/08820139.2020.1748047
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Represent an Immune Suppressive T Cell Checkpoint in Human Chronic Inflammatory Microenvironments

Abstract: Background: T cells present in chronic inflammatory tissues such as nasal polyps (from chronic rhinosinusitis patients) have been demonstrated to be hypo-responsive to activation via the TCR, similar to tumor-specific T cells in multiple different human tumor microenvironments. While immunosuppressive exosomes have been known to contribute to the failure of the tumorassociated T cells to respond optimally to activation stimuli, it is not known whether they play a similar role in chronic inflammatory microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The authors also show that blocking the cytokine IL-10, the immune checkpoint PD-L1, or both using monoclonal antibodies can reverse exosome-mediated immunosuppression. These two articles (Shenoy et al 2020 andShu et al 2020), along with many others published before, clearly demonstrate the role of exosomes in disease progression thereby establishing them as a therapeutic target, while offering possible strategies to target them. The article by Shu et al also showcases advances in technology for the detection and quantification of total and specific subsets of exosomes (such as those expressing PD-L1), which have come a long way since the initial discovery of these vesicles.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The authors also show that blocking the cytokine IL-10, the immune checkpoint PD-L1, or both using monoclonal antibodies can reverse exosome-mediated immunosuppression. These two articles (Shenoy et al 2020 andShu et al 2020), along with many others published before, clearly demonstrate the role of exosomes in disease progression thereby establishing them as a therapeutic target, while offering possible strategies to target them. The article by Shu et al also showcases advances in technology for the detection and quantification of total and specific subsets of exosomes (such as those expressing PD-L1), which have come a long way since the initial discovery of these vesicles.…”
Section: Introductionmentioning
confidence: 78%
“…The authors report that these exosomes protect macrophages from death mediated by Cisplatin-a chemotherapeutic agent used in cancer treatment, by arresting their proliferation, providing a classic example of the yin-yang effects of exosomes. The second article by Shenoy et al (Shenoy et al 2020) reports a study on exosomes derived from tissues associated with chronic inflammatory diseases such as chronic rhinosinusitis with nasal polyps (CRSwNP) and rheumatoid arthritis. The authors identify exosomes as an immune checkpoint that arrests T cell function, thus possibly contributing to the pathology of these chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 6 This makes PS an attractive target to neutralize in order to enhance immune responses in cancer, and possibly also in chronic inflammatory conditions, where a similar role for PS+ exosomes has been described. 30 Initial proof-of-concept studies showed that anti-PS antibody could reverse tumor exosome-mediated immunosuppression significantly. 6 Strategies to block PS in preclinical studies using anti-PS antibodies and annexin V or to treat lung cancer in clinical trials using a PS specific antibody, bavituximab, 23 have met with modest success, perhaps due to the relatively low PS-binding affinity of the molecules used and the relatively high molecular weight of the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to overcome this by generating additional tumor target cells derived from the patient's tumor in the future. We also plan to investigate the role of additional immune checkpoints such as other exhaustion markers (CTLA‐4, Tim‐3 and CD160), tumor‐associated exosomes 38–40 as well as exosome‐associated immunosuppressive lipids such as phosphatidylserine 41 and ganglioside GD3 42,43 in the observed tumor escape in future studies. The efficacy of checkpoint blockade can also be enhanced many fold with combination therapy, which can be tested rapidly in our model.…”
Section: Discussionmentioning
confidence: 99%